Neonatal iodine status survey by thyroid-stimulating hormone screening in Surabaya - Connie Untario; I Wayan Bikin Suryawan (Paediatrica Indonesiana, 2012)
Background Iodine deficiency disorders (lDD) are a significantpublic health problem globally. Iodine deficiency may causesubclinical hypothyroidism during pregnancy and early infancy.Neonatal thyroid screening of serum thyroidô€Šstimulating hormone(TSH) to detect hypothyroidism may also be used to determinethe prevalence of IDD in a population. Previous studies reportedmild ID D status in different parts of Indonesia.Objective To evaluate the iodine status of neonates born inMitra K eluarga Surabaya Hospital (MKSH) by TSH screeningover a 6ô€Šyear period.Methods T his is a crossô€Šsectional and hospitalô€Šbased studyconducted in MKSH from January 2005 to December 2010. Ofthe 5,619 infants born in MKSH during the study period, 3,349(59.6%) healthy infants took part in this study. Blood specimensfor TSH measurement were collected from subjects 2 to 6 daysafter birth, and sent to a reference laboraratory for evaluation.Using the neonatal TSH values, the iodine deficiency level ofthe group was determined according to the WHO/UNICEF/International Council for the Control of IDD criteria.Results A total of 3,349 newborn babies underwent neonatalTSH screening in MKSH. Subjects' mean TSH concentrationwas 5.14 mIU!L. A TSH concentration> SmIU!L was found in1270 (37.9%) subjects, 166 (27.6%) in 2005, 252 (44.0%) in 2006,331 (47.1 %) in 2007, 356 (57.7%) in 2008, 114 (20.7%) in 2009and 51 (16.8%) in 2010. On the basis of the WHO/UNICEF/International Council for the Control of Iodine DeficiencyDisorder criteria, this frequency corresponded to a moderate levelof IDD. Twentyô€Štwo neonates had TSH > 20 mIU!L from which2 infants were confirmed positive for hypothyroidism.Conclusion A 6ô€Šyear study of 3,349 newborns screened for TSHrevealed that 37.9% of subjects had TSH concentration of morethan SmIU!L. This frequency indicates a moderate level of IDDin the study population. [Paediatr Indones. 2012;52:289,93].